2005
DOI: 10.1111/j.1365-2494.2005.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

The productivity of oats and berseem clover intercrops. II. Effects of cutting date and density of oats on annual forage yield

Abstract: Annual forage yields of intercrops of berseem clover (Trifolium alexandrinum L.) and oats (Avena sativa L.), as affected by timing of initial harvest and sowing rate of oats, were investigated. Berseem clover was intercropped with oats at 0, 30, 60, 90 and 240 plants m )2 of oats in 1999 and 2000 in Alberta, Canada. Cutting date treatments involved initial harvest at 10-d intervals between 35 and 88 d after planting (DAP), and one or two subsequent harvests of regrowth. Total intercrop dry-matter (DM) yield av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(63 reference statements)
3
3
0
Order By: Relevance
“…Ross et al . () found CP contents ranging from 280 to 145 g CP kg −1 DM for black oat mixed with clover after 35 and 88 d respectively. Similarly, Moreira et al .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Ross et al . () found CP contents ranging from 280 to 145 g CP kg −1 DM for black oat mixed with clover after 35 and 88 d respectively. Similarly, Moreira et al .…”
Section: Discussionsupporting
confidence: 83%
“…The findings of Ross et al . () also corroborate these results: they obtained values of 520 and 305 g ADF kg −1 DM. Moreira et al .…”
Section: Discussionmentioning
confidence: 97%
“…We detach here that the CP concentration always decline with the plant age, as observed in figure 3f. Ross et al (2005) also found a decline from 310 to 180 g CP kg -1 DM for oats-clover mix at 35 and 88 days after planting, respectively, the same observed by other results in literature.…”
Section: Resultssupporting
confidence: 80%
“…Souza et al (2010) also reported no effect of P 2 O 5 application on the NDF content in Tanzania Additionally, the NDF and ADF of black oat were not affected by residual phosphate (Figure 5c and 5f). Ross et al (2005) found NDF levels of 520 g kg -1 DM and ADF levels of 305 g kg -1 DM of black oat, similar to the mean NDF levels found here, and slightly higher for ADF. Also, Moreira et al (2001) reported mean NDF levels of 482 g kg -1 DM and mean ADF levels of 277 g kg -1 DM.…”
Section: Resultssupporting
confidence: 70%
“…Therefore, it follows that alfalfa might have little plasticity among yield components where frequent defoliation increased tiller, diminished tiller mass, and resulted in no net change in forage yield (Chapman and Lemaire, 1993). To find appropriate cutting frequency to achieve tradeoff of higher quality and yields, researches had demonstrated that fertilization had significant effect on compensatory growth after cutting and increased forage fresh yield (Lei et al, 2005;Lithourgidis et al, 2006) and reduced yield loss from cutting (Ross et al, 2005). The present study results showed that forage yield decreased and forage quality improved at F40, which were in accordance with some other researches that cutting had significant effects on forage quality and yields (Chen et al, 2003;Yang et al, 2004).…”
Section: Variation ¶mentioning
confidence: 99%